Knowledge, attitude and practices of antibiotic usage among university students from Karachi, Pakistan - Limaye, Dnyanesh; Ziesenis, Patrick; Limaye, Vaidehi; Ahmad, Mansoor; Saeed, Farah; Rizvi, Ramla; Kapadi, Atul; Sathe, Sushama; Fortwengel, Gerhard (International Journal of Research in Medical Sciences, 2019)
Background: Antimicrobial resistance has become a serious global problem. A potential post-antibiotic era is threatening present and future medical advances. In Pakistan, the usage of antibiotic is unnecessarily high and due to over exposure to these drugs, bacteria are developing resistance against these drugs. It is necessary to improve public awareness about the rational use of antibiotics in order to bring a change in consumer’s behaviour. Therefore, present study was undertaken to assess the existing knowledge, attitude and practices related to antibiotic usage among university students. Methods: A cross-sectional study was carried out among university students from Karachi, Pakistan during May-June 2018. 200 students were approached to participate in the study of which 159 agreed to participate (males: 70, females: 89). Pretested questionnaire was distributed to the study subjects and the collected data was analyzed using IBM SPSS version 23. Results: Substantial number of (33% and 50%) participants were unaware about the differences in antibiotic: anti-inflammatory drugs and antibiotic: antipyretics respectively. 29% of the participants thought it is right to stop antibiotics only based on symptomatic improvement. Thirty nine percent and eighty three percent participants believed that antibiotics should always be prescribed to treat flu like symptoms and pneumonia respectively. Conclusions: Participants demonstrated average knowledge about antibiotics. Similarly, their attitude and practice toward antibiotic use was associated with misconceptions. An educational intervention is necessary to make them aware about rational use of antibiotics.